2011
DOI: 10.3892/mmr.2011.634
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step process of human breast carcinogenesis: A role for BRCA1, BECN1, CCND1, PTEN and UVRAG

Abstract: Abstract. In the female population in Asia, systematic investigation concerning alterations in cancer-related genes in breast carcinoma is rare, and the correlation among oncogene or suppressor gene expression with tumor cell apoptosis, cell cycle regulation and tumor cell autophagy remains to be clarified. In this study, a tissue microarray consisting of 360 individual samples from three different breast tissues was generated. By comparing the expression of the tumor-suppressor genes (BRCA1, BECN1, CCND1, PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…In combination of these findings, we speculated that the regulatory correlation between Beclin 1 and E-cadherin depended on the cell types. Reportedly, loss and down-regulation of Beclin 1 expression was immunohistochemically observed in esophageal adenocarcinoma (64), colorectal cancer (65), breast cancer (66), but versa in pancreatic cancer (67). Here, we performed meta-analysis and found that down-regulated Beclin 1 expression in gastric cancer was positively linked to lymph node metastasis, TNM staging, dedifferentiation and poor prognosis, in agreement with our bioinformatics findings.…”
Section: Discussionsupporting
confidence: 88%
“…In combination of these findings, we speculated that the regulatory correlation between Beclin 1 and E-cadherin depended on the cell types. Reportedly, loss and down-regulation of Beclin 1 expression was immunohistochemically observed in esophageal adenocarcinoma (64), colorectal cancer (65), breast cancer (66), but versa in pancreatic cancer (67). Here, we performed meta-analysis and found that down-regulated Beclin 1 expression in gastric cancer was positively linked to lymph node metastasis, TNM staging, dedifferentiation and poor prognosis, in agreement with our bioinformatics findings.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with earlier studies of BECN1 in small cohorts of patients with breast cancer. Levels of BECN1 mRNA expression have been reported to be reduced in breast cancer ( Li et al, 2010 , Wu et al, 2012b ) and have been associated with poor differentiation, and increased tumor size, proliferation and risk of metastasis ( Wu et al, 2012b , Yao et al, 2011 ). In small datasets, low BECN1 mRNA expression was associated with triple-negative breast cancer ( Cicchini et al, 2014 ) and with worse prognosis regardless of ER status ( Perou et al, 2000 , Dong et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is a phosphatase that acts as a tumor suppressor by inhibiting the PI3K/AKT signaling pathway. PI3K is essential for the activation of AKT; a serine/threonine kinase necessary for cell survival and growth 100,101 . PTEN along with other tumor suppressor genes like BRCA1 , BECN1 and UVRAG lead to the development of human breast cancer via dysregulated expression of mRNA 100 .…”
Section: Regulatory Factors With Mechanismsmentioning
confidence: 99%